Tanzania : Country Procurement Assessment Report, Executive Summary - World Bank (Washington, DC, 2013)
This Country Procurement Assessment Report (CPAR)intends to determine the compatibility of national procurement law, and practices, with the principles of economy, and with international procurement practices. This CPAR, the second of its kind in Tanzania, looks at the legislative framework, the performance of regulatory functions, the enforcement regime, and the capacity of public sector institutions to conduct procurement, including the effects of corruption on procurement. Recommendations suggest to disseminate the new Local Government Authority Procurement regulations, and, establish the Public Procurement Appeals Authority with its necessary amendments of decentralizing procurement operations, while introducing mandatory time limits on various steps in the procurement process. Current procedures, and practices should further enforce rules on advertising, pre-qualification, submission and opening of bids, and the use of an evaluation criteria through regular audits, and effective sanctions. In addition, a credible complaints mechanisms should be in place, by strengthening the capacity of the Central Tender Board (CTB). In the short-term, operational, and regulatory functions should be separated from the CTB, decentralizing procurement to the ministerial level, establishing a Regulatory Authority (RA) to report directly to the Minister of Finance. In the medium-term, an information management system should link the RA with procuring entities, and, for the long-term, Government stores should be closed, introducing instead a system based on framework agreements.